OxLDL/LOX-1 mediated sex, age, stiffness, and endothelial dependent alterations in mouse thoracic aortic vascular reactivity - Wendt, Trevor S.; Ansar, Saema; Gonzales, Rayna J. (Frontiers in Physiology, 2024)
Elevated levels of oxidized low-density lipoprotein (oxLDL) are not just a risk factor and key component that acerates and worsens cardiovascular disease fueling inflammation, plaque buildup and vascular damage. OxLDL can elicit its detrimental action via lectin-like oxLDL receptor 1 (LOX-1). In this study, we determined whether oxLDL, via LOX-1, alters aortic vascular reactivity and determined if sex and age differences exist. Thoracic aortic endotheliumintact or -denuded ring segments were isolated from 7 and 12 mo. old intact C57BL/6J female and male mice and pre-incubated with oxLDL ex vivo (50ug/dL; 2h). Using wire myography, cumulative concentration-response curves to phenylephrine (PE) were generated to determine contractile responses. From these curves, the EC50 was determined and used to contract rings to assess acetylcholine (ACh) dependent relaxation. Calculated aortic stiffness and remodeling were also assessed. BI-0115 (10𝜇𝜇M; selective LOX-1 inhibitor) was used to determine LOX-1 dependence. We observed differential sex, age, endothelial cell, and LOX-1 dependent alterations to the efficacy of PE-induced contractile responses and ACh-mediated vasorelaxation in the thoracic aortic rings following oxLDL exposure. Additionally, we observed a distinct sex and age effect on thoracic aortic stiffness following exposure to oxLDL. There was also a sex effect on calculated vessel diameter, as well as an age effect on oxLDL-mediated aortic remodeling that was LOX-1 dependent. Thus, LOX-1 inhibition and the resulting attenuation of oxLDL/endothelial-mediated alterations in aortic function suggests that there are differential sex differences in the role of oxLDL/LOX-1 in the thoracic aorta of middle-aged male and female mice.We investigated the effects of oxidized low-density lipoprotein (oxLDL) via the LOX-1 receptor on murine thoracic aortic vasoreactivity, stiffness, and remodeling across age and sex. Acute exposure to oxLDL led to altered vasoreactivity, endothelial dysfunction, and changes in aortic stiffness and remodeling. These effects were in-part age, sex, endothelial, and LOX-1 dependent.This study reveals potential complex interactions in oxLDL/LOX-1-mediated vascular responses that could serve as potential therapeutic intervention for vascular diseases such as atherosclerosis and stroke.